(untitled) (Bangladesh Journal of Zoology, 2017)
Fecal samples (total 707; 290 asymptomatic and 417 symptomatic) were collected during June 2014 to May 2015 from 145 children of Mirpur slum area. In diarrhoeal children, the average prevalence was the topmost for Trichuris trichiura (24.16%); peak among the children aged nine to ten months (38.81%); following Ascaris lumbricoides (7.44%). Overall soil transmitted helminth (STH) infestation was the highest (10.5%) in October, 2014 (non-diarrhoeal) and in diarrhoeal children, it was the highest (14.45%) in April, 2015. Mixed infection was less frequent (23.62%). The STH infestation was significant (p < 0.05) among the discontinuously breast-fed children (96.23%), the children of illiterate mothers (85.19%), living in poor housing (88.46%), having diarrhoea in the family members (84.78%) and among the children who experienced highest frequency (7 to 9 times in a year) of diarrhoea. Efficacy of pentaplex PCR-Luminex assay was evaluated for the simultaneous detection of STH compared to direct microscopy which showed less sensitivity (0 - 11.11%) than PCR-Luminex. Bangladesh J. Zool. 44(2): 219-228, 2016